Comparison of video laryngoscopy with direct laryngoscopy for intubation success in critically ill patients: a systematic review and Bayesian network meta-analysis - Kim, Jae Guk; Ahn, Chiwon; Kim, Wonhee; Lim, Tae-Ho; Jang, Bo-Hyong; Cho, Youngsuk; Shin, Hyungoo; Lee, Heekyung; Lee, Juncheol; Choi, Kyu-Sun; Na, Min Kyun; Kwon, Sae Min (Frontiers in Medicine, 2023)
Introduction This review compares the efficacy of video laryngoscopy (VL) with direct laryngoscopy (DL) for successful tracheal intubation in critically ill or emergency-care patients. Methods We searched the MEDLINE, Embase, and Cochrane Library databases for randomized controlled trials (RCTs) that compared one or more video laryngoscopes to DL. Sensitivity analysis, subgroup analysis, and network meta-analysis were used to investigate factors potentially influencing the efficacy of VL. The primary outcome was the success rate of first-attempt intubation. Results This meta-analysis included 4244 patients from 22 RCTs. After sensitivity analysis, the pooled analysis revealed no significant difference in the success rate between VL and DL (VL vs. DL, 77.3% vs. 75.3%, respectively; OR, 1.36; 95% CI, 0.84–2.20; I2 = 80%; low-quality evidence). However, based on a moderate certainty of evidence, VL outperformed DL in the subgroup analyses of intubation associated with difficult airways, inexperienced practitioners, or in-hospital settings. In the network meta-analysis comparing VL blade types, nonchanneled angular VL provided the best outcomes. The nonchanneled Macintosh video laryngoscope ranked second, and DL ranked third. Channeled VL was associated with the worst treatment outcomes. Discussion This pooled analysis found, with a low certainty of evidence, that VL does not improve intubation success relative to DL. Channeled VL had low efficacy in terms of intubation success compared with nonchanneled VL and DL. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=285702, identifier: CRD42021285702.